Využití finanční analýzy v podniku - Doležel, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Diplomová práce pojednává o analýze účetních výkazů, a to rozvahy, zisků a ztrát a cash-flow podniku za určité časové období, prostřednictvím finanční analýzy. Obsahuje jednak teoretická východiska finanční analýzy, jednak postupy potřebné k úspěšné analýze, ale také samotnou analýzu vybraných položek účetních výkazů, k naplnění cílů diplomové práce.

This master work deals with analysis of financial statement and that’s balance sheet, profits and losses and cash-flow of company at specific period through the use of financial analysis. It’s includes in part theoretical background of financial analysis, in part directions needed to successful analysis and analysis of chosen financial statements items to fulfill objectives of master work.
Application of Financial Analysis in a Company
Keywords: Finanční analýza; rozdílové ukazatele; poměrové ukazatele; soustavy ukazatelů; Financial Analysis; differential characteristics; financial ratios; system indicators